2022
DOI: 10.3390/polym14030443
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Curcumin Microemulsions by Coupling of KLVFF Peptide: A Prototype for Targeted Bifunctional Microemulsions

Abstract: Curcumin is one of the most promising natural therapeutics for use against Alzheimer’s disease. The major limitations of curcumin are its low oral bioavailability and difficulty in permeating the blood–brain barrier. Therefore, designing a delivery system of curcumin to overcome its limitations must be employed. KLVFF, a peptide known as an amyloid blocker, was used in this study as a targeting moiety to develop a targeted drug delivery system. A prototype of transnasal KLVFF conjugated microemulsions containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
(93 reference statements)
1
6
0
Order By: Relevance
“…Therefore, the ability to block only the derangement of this protein could be relevant to the success of the amyloid-based strategy. Different compounds can interfere with amyloid aggregation and, in particular, promising results have been obtained using amyloid fragments [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the ability to block only the derangement of this protein could be relevant to the success of the amyloid-based strategy. Different compounds can interfere with amyloid aggregation and, in particular, promising results have been obtained using amyloid fragments [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The KLVFF-based prototypes have been extensively discussed in the literature [ 16 , 17 , 18 ]. The scientific community agrees on the anti-aggregative properties of this small fragment [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous result, the suitable formulation consisted of oleic acid as the oil phase, a mixture of Tween 80 and KLVFF-Pluronic F127 in the ratio 1:1 (surfactant), ethanol (co-surfactant) as a mixture of surfactant and co-surfactant (S mix ), and water as the aqueous phase. We reported that the most suitable ME component was 15:80:5 for the oil:S mix :water ratio, respectively [ 71 ] This microemulsion component exhibited optimal results and was chosen to create KCME in this study. Curcumin (0.9 mg/mL) was dissolved in the oil phase by adding the required amount of S mix and water and stirring to create a clear, yellow, and transparent dispersion.…”
Section: Methodsmentioning
confidence: 99%
“…Although Pen-functionalized nanoparticles can cross the BBB, the nanoparticles still hardly accumulated in the lesion site due to the lack of targeting capability. As for delivery of Aβ inhibitors, KLVFF from the central hydrophobic core (CHC) region of Aβ can serve as an Aβ-targeting peptide [ 39 ]. For instance, Plissonneau et al grafted KLVFF onto nanoparticles, thereby conferring upon them the ability to recognize and bind to amyloid plaques in the mouse hippocampus [ 40 ].…”
Section: Introductionmentioning
confidence: 99%